Zakah compliance behavior among entrepreneurs: economic factors approach - Nashwan, Saeed Awadh; Abdul Jabbar, Hijattulah; Abdul Aziz, Saliza; Haladu, Alhassan (Emerald Publishing Limited, 2020)
Purpose – As one of the constituted main pillars of Islam, Zakah compliance (ZC) is mandated upon Muslims from all studies of life. Taking the disappointingly low compliance level in developing countries, including Yemen, as its backdrop, the purpose of this study is to investigate ZC behavior among entrepreneurs, drawing on the economic approach perspective. Design/methodology/approach – The study adopted a cross-sectional design based on a survey of entrepreneurs in Yemen. It used primary data collected via self-administered questionnaires, involving a sample of 500 participants. A variance-based structural modeling equation-partial least squares were used to measure the instruments and assess the hypothesized relationships. Findings – The findings affirmed the suitability of the economic factors approaches in the context of ZC in a developing country. Specifically, the study demonstrated that Zakah law complexity has a significant negative influence on ZC of entrepreneurs. It also found a significant positive relationship between religiosity and ZC among the study sample, whereas the study revealed that law enforcement has no influence on compliance behavior.Practical implications – Policies and programs focused on Zakah laws and regulations could be formulated to make them less complex and simpler for acceptable levels of ZC. The result is further relevant to policymakers in Muslim communities to strengthen the religious faith of Zakah payers toward compliance with one of the fundamental religious obligations such as Zakah.Originality/value – This study enriches the limited previous studies on actual ZC from the perspective of developing communities, especially Yemen. Most importantly, the value was added to the limited literature internationally from an economic aspect.